Keamanan Pangan untuk Semua - Adhi S Lukman; Feri Kusnandar (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2015)
Food safety requirement must be fulfilled by food producers in all food chain in order to ensure the product safety when arrives to consumers. The government is responsible for protecting public by setting rules and oversight in whole food supply chain. Enforcement of food safety regulations and intensive oversight by government in the production and distribution of food needs to be applied in an integrated manner without any discrimination, either food types or business scale of food producers. Continuous efforts should be made to raise public awareness of the importance of food safety as well as strengthen the national food safety management system.